2004
DOI: 10.1021/jm0496685
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between an Amantadine Analogue and the Transmembrane Portion of the Influenza A M2 Protein in Liposomes Probed by1H NMR Spectroscopy of the Ligand

Abstract: 1H NMR spectroscopy of a fluoroamantadine ligand was used to probe the pH dependence of binding to the transmembrane peptide fragment of the influenza A M2 proton channel (M2TM) incorporated into 1,2-dimyristoyl-sn-glycero-3-phosphocholine liposomes. Above pH 7.5, when M2TM bound the ligand, fluoroamantadine resonances became too broad to be detected. Fluoroamantadine interacted weakly with the liposomes, indicating it may first bind to the bilayer and then block target channels after diffusion across the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Because there is no barrier for the absorption of amantadine or rimantadine to occupy an interfacial location (Fig. 2 B), these results support the idea that these compounds could first partition into the bilayer before interacting with its target protein (91,92). Moreover, several mutations of the M2 channel (93,94) that confer amantadine resistance to influenza A (at residue positions 26, 27, 30, 31, or 34) are located at a position in the bilayer that could be readily accessible from amantadine that has already absorbed to the interface as well as from the aqueous solution.…”
Section: Implications For Adamantanes As Drugssupporting
confidence: 66%
“…Because there is no barrier for the absorption of amantadine or rimantadine to occupy an interfacial location (Fig. 2 B), these results support the idea that these compounds could first partition into the bilayer before interacting with its target protein (91,92). Moreover, several mutations of the M2 channel (93,94) that confer amantadine resistance to influenza A (at residue positions 26, 27, 30, 31, or 34) are located at a position in the bilayer that could be readily accessible from amantadine that has already absorbed to the interface as well as from the aqueous solution.…”
Section: Implications For Adamantanes As Drugssupporting
confidence: 66%
“…182 The complex was studied in dodecylphosphocholine (DPC) micelles. In earlier work, the lineshape of 1 H resonances of 96 had been utilized 183 and found to give resonances too broad to be detected above pH 7.5, when the open-channel binding of amantadine to the M 2 channel is expected to occur. When using 19 F NMR, this could be circumvented and the authors found that the homotetramer of their fluorinated M 2 TM model peptide appears at pH 7, which is ~ 0.5 units below the pH threshold reported before using CD spectroscopy as the experimental method.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…The synthesis of aminoadamantane compounds 3-9 has been described in ref. [66][67][68][69] , and the synthesis of Table S1). …”
Section: Experimental Protocolmentioning
confidence: 99%